(3CQHYhf MOjKkGs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s ((3Ydi QVG Hf eQJVi GdMSjfj fgQGQhOj s)
(3ChdgG (B:s
(3hHYO aEf GdabjQ Edi Gddg GdZfi HgGA GdOjf eMeO GdYGedjhgPg CQHYhf MOjKkG ef WQb Cgd HjJ GdfHhI hGdhdGjI LeYJgG ef GeGcf YOjOI hehGWf TQjOI s
(3BNQgG (B:s
(3hCfJ JYde CQHGH GdCQUGO GdQheGfjg CYdi bOQkG hCQaY TCfkG ef CUMGH GdCQUGO GdLSeGfjI hgG gfG CbWY GdcdGe s
(3GdfSNI HgG MhGTs
(3fSNI Chdi HBNQgG Jedcs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
Keywords: (3GdMOjK h GdeUWdMs